Adaptive control strategies for button motor actuated insect scale flapping wing MAV mechanisms - Singh, Spoorthi; Jain, Meet Hitesh; Kaushal, Kanishk; Zuber, Mohammad; Basri, Ernnie Illyani; Ahmad, Kamarul Arifin; Dol, Sharul Sham; Nair, Vishnu G. (Nature Research, 2025)
The development of Flapping Wing Micro Aerial Vehicles (FWMAVs) has gained significant attention due to their potential for energy-efficient, lightweight, and highly maneuverable flight inspired by nature. This study presents innovative designs and adaptive control strategies for insect-scale FWMAVs, utilizing compact button vibrator motors as actuators for wing flapping. These actuators offer advantages in size, weight, and power efficiency but pose challenges in achieving continuous and controlled motion due to mechanical, control, and durability constraints. The research explores multiple lever alignment configurations using simplified crank-slider mechanisms, driven by single and dual coreless DC motors powered by a 1–3.7 V DC supply. Detailed modeling in SIMSCAPE Multibody and structural movement analysis using Compmech GIM software facilitate the evaluation of variations in flapping frequency, velocity, and acceleration. Advanced control strategies, including Self-Regulatory Fractional Fuzzy Control (SRFFC) and Fractional PID (FPID), are assessed under simulated and real-world conditions to mitigate external disturbances. Additionally, an AI-based disturbance observer is implemented to enhance stability and optimize power efficiency by compensating for environmental disturbances. Performance metrics such as rise time, settling time, overshoot, and integral absolute error (IAE) demonstrate the superior efficiency and disturbance rejection capabilities of SRFFC compared to FPID. Experimental validation and real-time assessments of maneuvering capabilities, including leftward, rightward, and forward movements, further substantiate the proposed strategies. This study underscores the potential of SRFFC-driven designs and modular motor configurations to enhance the performance, control, and applicability of FWMAVs for advanced micro-aerial systems.